2020
DOI: 10.3390/molecules25163705
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Factors Affecting Microtubule Dynamics in Normal and Cancer Cells

Abstract: Microtubules (MTs), highly dynamic structures composed of α- and β-tubulin heterodimers, are involved in cell movement and intracellular traffic and are essential for cell division. Within the cell, MTs are not uniform as they can be composed of different tubulin isotypes that are post-translationally modified and interact with different microtubule-associated proteins (MAPs). These diverse intrinsic factors influence the dynamics of MTs. Extrinsic factors such as microtubule-targeting agents (MTAs) can also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 291 publications
(457 reference statements)
0
48
0
Order By: Relevance
“…Artemisinin, a repurposed cytotoxic natural product derived from Artemisia annua L. shows potent cytotoxicity against retinoblastoma cell lines, while it shows low cytotoxicity on normal retina cell lines ( Lichota and Gwozdzinski, 2018 ). The changes in the cell surface, microtubule remodeling, dysfunctional ROS scavenging system, cell cycle, and DNA repair mechanisms are some of the parameters which are significantly altered in cancer cells as compared to normal cells, leading to different mode of action of natural products and different cytotoxicity on the normal and cancer cells ( Borys et al, 2020 ). Doxorubicin, on the other hand is a potent anticancer drug, but has been known for several side effects, including non-targeted cytotoxicity ( Ibiyeye et al, 2019 ).…”
Section: Treatment Of Ase Resulted In Interference With Cell Viability Progression In Cell Cycle and Cell Nuclear Morphology In Hela Cellmentioning
confidence: 99%
“…Artemisinin, a repurposed cytotoxic natural product derived from Artemisia annua L. shows potent cytotoxicity against retinoblastoma cell lines, while it shows low cytotoxicity on normal retina cell lines ( Lichota and Gwozdzinski, 2018 ). The changes in the cell surface, microtubule remodeling, dysfunctional ROS scavenging system, cell cycle, and DNA repair mechanisms are some of the parameters which are significantly altered in cancer cells as compared to normal cells, leading to different mode of action of natural products and different cytotoxicity on the normal and cancer cells ( Borys et al, 2020 ). Doxorubicin, on the other hand is a potent anticancer drug, but has been known for several side effects, including non-targeted cytotoxicity ( Ibiyeye et al, 2019 ).…”
Section: Treatment Of Ase Resulted In Interference With Cell Viability Progression In Cell Cycle and Cell Nuclear Morphology In Hela Cellmentioning
confidence: 99%
“…It is also worth highlighting the alterations in the dynamics of microtubules and tubulin, which may influence the binding of the anti-tumor agent [ 162 ]. Therefore, an altered expression of tubulin isotypes is considered a prognostic marker of chemotherapy drug resistance and survival [ 163 , 164 ]. In fact, many studies have shown the expression of different α and β tubulin isotypes in cancer cells.…”
Section: The Fight Against Drug Resistancementioning
confidence: 99%
“…In fact, many studies have shown the expression of different α and β tubulin isotypes in cancer cells. Moreover, the isotype expression depends on the type of tumor [ 163 ]. Therefore, high levels of αIIb tubulin in hepatocellular carcinoma; βI in ovarian cancer and NSCLC adenocarcinoma; βII in lung adenocarcinoma; βIII in colon cancer, uterine serous carcinoma, and melanoma; and βV in NSCLC, are associated with a resistance to PTX [ 165 , 166 , 167 , 168 , 169 , 170 , 171 ].…”
Section: The Fight Against Drug Resistancementioning
confidence: 99%
“…Microtubules, dynamic intracellular polymers of tubulin, form part of the cytoskeleton and perform key functions in important processes such as mitosis, intracellular transport, and migration. Microtubule-directed small molecules, which inhibit the dynamics of a microtubule, are often used clinically as valuable tools in cell biology and chemotherapeutics, due to their ability to perturb mitosis [1][2][3]. Tumor cells have a greater capacity for cell proliferation and are also more susceptible to damage from microtubule inhibitors.…”
Section: Introductionmentioning
confidence: 99%